Hastings Alumni and Fresno County Bar Association Joint Luncheon with California Supreme Court Justice Wiley Manuel - Watkins, Howard::::::::: (1979)
Justice Wiley Manuel speaking; head table Howard Watkins, Baxter Richardson, David St. Louis, Libby Strobe